Stress, genes, and generalizability across gender: effects of maoa and stress sensitivity on crime and delinquency - Wells, Jessica (Criminology, 2017)
In the current study, we extend the gene-by-environment interaction (cGxE) literature by examining how a widely studied polymorphism, the MAOA upstream variable number tandem repeat (MAOA-uVNTR) interacts with distal and proximal stressors to explain variation in crime and delinquency. Prior research findings have revealed that MAOA-uVNTR interacts with single indicators of environmental adversity to explain criminal behavior in general-population and incarcerated samples. Nevertheless, the genetically moderated stress sensitivity hypothesis suggests that increased risk for criminal behavior associated with variation in the MAOA-uVNTR can be best understood in the context of both distal stress during childhood and proximal stress in adulthood. Therefore, we employed Tobit regression analyses to examine a gene–distal–proximal environment (CGxExE) interaction across gender in a sample of university students (n = 267) and with data from the National Longitudinal Study of Adolescent to Adult Health (Add Health; n = 1,294). The results across both sets of analyses demonstrate that variation in the MAOA-uVNTR interacts with distal and proximal stress to lead to increased risk for criminal behavior in males. Although proximal life stress is associated with an increase in crime and delinquency, this effect is more pronounced among MAOA-L allele carriers that have experienced distal stress.